1973
DOI: 10.1111/j.1755-3768.1973.tb03794.x
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Central Retinal Angiopathy

Abstract: A family, with three members affected by a central retinal angiopathy, is reported. The fundus changes consisted of tortuous arterioles, ectatic capillaries, microaneurysms, small retinal haemorrhages and tiny white dots. The changes were demonstrated by colour fluorescein angiography. The retinal changes simulate those described in hereditary haemorrhagic teleangiectasia (Rendu-Osler-Weber's disease) and in familial retinal arteriolar tortuosity, both showing dominant inheritance. Although none of the three p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Additionally, Ehlers and Jensen described three family members in successive generations with perifoveal telangiectasis and capillary loss. 1,6 Although our patient did not have either a family history or any evidence of neurologic disease, it is possible that he has a unique manifestation of cerebroretinal vasculopathy. The clinical appearance of the patients in Grand's series is similar to our patient.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Additionally, Ehlers and Jensen described three family members in successive generations with perifoveal telangiectasis and capillary loss. 1,6 Although our patient did not have either a family history or any evidence of neurologic disease, it is possible that he has a unique manifestation of cerebroretinal vasculopathy. The clinical appearance of the patients in Grand's series is similar to our patient.…”
Section: Discussionmentioning
confidence: 83%
“…The two largest series are by Gass and Blodi 1 and by Grand et al 5 , otherwise, only a few patients have been reported. 3,6 In a retrospective review of 140 patients with idiopathic juxtafoveal retinal telangiectasis seen over a 28-year period, Gass and Blodi described 7 cases with obliterative changes. 1,2 Each of these patients had either systemic (Group 3A) or cerebral vascular occlusive disease (Group 3B), which the authors believe contributed to their eye disease.…”
Section: Discussionmentioning
confidence: 99%